Ten Tips for Organizing a Videoconference at Multiple Sites Using the Polycom® System - Michael G. Andreu; Melissa H. Friedman (EDIS)
FOR-122, a 4-page fact sheet by Michael G. Andreu and Melissa H. Friedman, enumerates 10 steps to follow when coordinating a multi-site videoconference event using IFAS videoconferencing facilities. Published by the UF School of Forest Resources and Conservation, April 2007.